A sintered R-Fe-B permanent magnet and its preparation method and application

By introducing RH-rich grain boundaries and composite main phase grains with core-shell structures into the R-Fe-B permanent magnet, and adopting composite diffusion treatment, the problem of degradation of magnetic properties caused by the addition of La and Ce elements in the prior art is solved, and a high coercive force and high performance sintered NdFeB magnet is achieved.

CN115410786BActive Publication Date: 2025-04-25NANTONG ZHENGHAI MAGNET CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210962847.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-11
Publication Date
2025-04-25
Estimated Expiration
2042-08-11

AI Technical Summary

Technical Problem

When the prior art adds La and Ce elements to the sintered neodymium iron boron magnet, it is easy to reduce magnetic performance, and the process is complicated and cost-effective, making it difficult to effectively improve the coercive force of the magnet.

Method used

By introducing grain boundaries and composite main phase grains into the R-Fe-B permanent magnet, the grain boundaries are rich in RH (such as Dy, Tb, Ho) elements. The main phase grains have a core-shell structure, and through composite diffusion treatment, the uniform diffusion of heavy rare earth elements inside the magnet is ensured.

Benefits of technology

It significantly improves the coercive force and squareness of the magnet, improves the resistance to high-temperature demagnetization, and improves the overall magnetic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115410786B_ABST
    Figure CN115410786B_ABST
Patent Text Reader

Abstract

The present invention provides a sintered R-Fe-B permanent magnet and a preparation method and application thereof. The permanent magnet includes at least grain boundaries and composite main phase grains; the grain boundaries include RH-rich phases, which are distributed in the grain boundaries between composite main phase grains in agglomerates, preferably at the intersection of any three or more adjacent composite main phase grains; the RH-rich phase is continuously distributed along the grain boundaries in a thin layer and band; the RH content in the grain boundaries is greater than the RH content in the main phase grains; the composite main phase grains have a core-shell structure, and the core-shell structure includes a core structure with an R-T-B type phase structure, and a shell structure on the outer layer of the core structure; the core structure includes Ce-rich main phase grains and Ce-poor main phase grains. The permanent magnet prepared by the present invention has high coercive force magnetic properties and squareness, and significantly improves the ability of the magnet to resist high-temperature demagnetization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet material preparation, and in particular relates to a grain boundary diffusion sintered R-Fe-B permanent magnet and a preparation method and application thereof. Background Art

[0002] Sintered NdFeB, as the third generation of rare earth permanent magnet materials, is mainly composed of rare earth PrNd, iron, boron and other elements. Due to its excellent magnetic properties and high cost performance, it is widely used in various rare earth permanent magnet motors, smart consumer electronics, medical devices and other fields. With the rapid development of low-carbon environmental protection economy and high-tech, the demand for sintered NdFeB magnets is growing, which has greatly driven the consumption of rare earth PrNd resources and caused the price of PrNd to gradually increase. La and Ce, as rare earth elements with similar chemical properties to PrNd and the most abundant reserves, are limited in their application in the field of rare earth permanent magnet materials due to their own low intrinsic magnetic properties. At present, how to increase the use of La and Ce elements and reduce costs without affecting the magnetic properties has become one of the research topics for saving rare earths.

[0003] In the prior art, there are mainly the following ways to add La and Ce into magnets: the first is to add them by alloying, that is, adding metal La and Ce raw materials during the smelting process; the second is to add them by dual alloying, that is, first smelting and preparing (R, LaCe)-Fe-B and R-Fe-B alloy flakes (R is selected from one or more of Nd, Pr, Dy, Tb, Ho, Gd), and then mixing the above alloy flakes in a certain proportion and pressing and sintering; the third is to attach La and Ce compounds or alloys on the surface of the magnet, and undergo appropriate heat treatment process to diffuse La and Ce into the interior of the magnet.

[0004] In the above method, adding La and Ce by alloying will cause La and Ce to enter the main phase grains, thereby reducing the saturation magnetic polarization intensity, Curie temperature, magnetocrystalline anisotropy field and other properties of the main phase grains, thereby reducing the initial performance of the magnet, thereby limiting its application development; however, adding La and Ce by diffusion has technical defects such as complicated and cumbersome process, insufficient amount of La and Ce added, and difficulty in improving the coercive force of the magnet, so it has low cost performance and is not conducive to its application development. The dual alloying method can prevent La and Ce from entering the main phase grains to a certain extent, and therefore has gradually become the mainstream preparation process for NdFeB magnets containing La and Ce.

[0005] However, in order to achieve the preparation of high-performance La and Ce-containing NdFeB magnets, in order to compensate for the reduction in magnetic properties caused by the addition of La and Ce, a certain amount of heavy rare earth elements such as Dy and Tb are usually added when preparing La and Ce-rich magnets to improve the magnetic properties of the magnets. The heavy rare earth grain boundary diffusion technology is currently the most effective and easiest method to implement. Therefore, some studies have superimposed NdCeFeB dual alloys and grain boundary diffusion technology to prepare high coercive force magnets, but the performance of the resulting magnets is not as good as expected, mainly due to the fact that the grain boundary phase composition and grain boundary structure of the diffusion substrate magnet in the heavy rare earth grain boundary diffusion technology have a decisive role in the penetration of heavy rare earth and its flow and dispersion inside the magnet.

[0006] In the NdCeFeB magnets prepared by the dual alloy method, due to the difference in composition between the main and auxiliary phases, there is a significant concentration difference in the constituent elements, which seriously affects the penetration of heavy rare earth elements into the interior of the magnet, and the final increase in the coercivity of the magnet is not obvious. Due to the heterogeneity of the distribution of rare earth elements in the two main phases, the grain boundary diffusion of heavy rare earth involves multiple situations. On the one hand, it diffuses and replaces Nd in the Nd2Fe14B main phase, and on the other hand, it diffuses and replaces Ce in the Ce2Fe14B main phase. The two processes compete with each other, and the replaced Nd or Ce will further undergo a diffusion substitution process, resulting in the heavy rare earth being replaced into the main phase, making the utilization rate of heavy rare earth low, resulting in poor coercivity of the magnet after diffusion. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides an R-Fe-B permanent magnet with high coercivity and a preparation method and application thereof.

[0008] The present invention provides an R-Fe-B permanent magnet, which comprises at least grain boundaries and composite main phase grains;

[0009] The grain boundary includes an RH-rich phase, and the RH-rich phase is distributed in the grain boundary between the composite main phase grains in a massed form, preferably at the intersection of any three or more adjacent composite main phase grains; the RH-rich phase can also be distributed continuously along the grain boundary in a thin layer band;

[0010] The content of RH in the grain boundary is greater than the content of RH in the main phase grains, and RH is selected from at least one of heavy rare earth metals such as Dy, Tb, and Ho;

[0011] The composite main phase grains have a core-shell structure, wherein the core-shell structure includes a core structure having an RTB-type phase structure and a shell structure on the outer layer of the core structure;

[0012] The core structure includes Ce-rich main phase grains and Ce-poor main phase grains; the Ce content in the Ce-rich main phase grains is 1-15wt%; the Ce content in the Ce-poor main phase grains is 0-1wt%.

[0013] According to an embodiment of the present invention, the content of RH in the grain boundary is preferably greater than the content of RH in the shell structure.

[0014] According to an embodiment of the present invention, the content of RL in the shell structure is greater than or equal to the content of RL in the core structure.

[0015] According to an embodiment of the present invention, RL is selected from at least one of light rare earth metals such as Pr and Nd.

[0016] According to an embodiment of the present invention, the permanent magnet has Figure 1 The structure shown in the figure, the permanent magnet comprises at least: grain boundaries and composite main phase grains, wherein the composite main phase grains have a core-shell structure, the core structure comprises Ce-rich main phase grains and Ce-poor main phase grains, and the outer layer of the core structure has a shell structure; the content of RL in the shell structure is greater than or equal to the content of RL in the core structure, and the content of RH in the grain boundaries is greater than the content of RH in the main phase grains.

[0017] According to an embodiment of the present invention, the RTB-type phase structure includes at least the following components:

[0018] R, whose weight percentage is 28%≤R≤35%; R is selected from neodymium (Nd) and cerium (Ce), and optionally includes or excludes at least one of scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu);

[0019] B, the weight percentage of which is 0.8%≤B≤1.2%;

[0020] M, whose weight percentage is 0≤M≤5%; M is selected from at least one of aluminum (Al), titanium (Ti), copper (Cu), gallium (Ga), zirconium (Zr), and niobium (Nb);

[0021] The balance is T; T is selected from iron (Fe), and optionally includes or excludes cobalt (Co).

[0022] According to an embodiment of the present invention, the permanent magnet is prepared by mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy, pressing and molding, sintering, and then performing composite diffusion.

[0023] Preferably, in the low-Ce main alloy, the Ce content is no more than 1wt%, preferably 0-1wt%.

[0024] Preferably, in the high-Ce auxiliary alloy, the Ce content is greater than 1wt% and not greater than 15wt%.

[0025] According to an embodiment of the present invention, the permanent magnet has the phase structure of grain boundaries and composite main phase grains from the surface to the core. The core of the permanent magnet in the present invention refers to a position at least 500 μm away from the magnet surface.

[0026] According to the embodiment of the present invention, the content of Ce in the grain boundary phase is not specifically limited.

[0027] The present invention also provides a method for preparing the above-mentioned permanent magnet, which comprises mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy, pressing and molding the mixture, and sintering the mixture to obtain a green body, and preparing the permanent magnet through composite diffusion of the green body.

[0028] Preferably, in the low-Ce main alloy, the Ce content is not more than 1wt%, preferably 0-1wt%, for example 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8 wt%, 0.9wt%, 1wt%.

[0029] Preferably, in the high-Ce auxiliary alloy, the Ce content is greater than 1wt% and not more than 15wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%.

[0030] According to an embodiment of the present invention, the powder of the low Ce main alloy and the powder of the high Ce auxiliary alloy can be prepared by methods known in the art, for example, by hydrogen crushing, dehydrogenation, and grinding of alloy flakes. The hydrogen crushing, dehydrogenation, and grinding can be performed by methods known in the art.

[0031] Exemplarily, a low-Ce main alloy is prepared to obtain main alloy flakes, and then the main alloy flakes are subjected to hydrogen crushing, dehydrogenation, and grinding to prepare low-Ce main alloy powder.

[0032] Exemplarily, a high-Ce auxiliary alloy is prepared to obtain auxiliary alloy flakes, and then the auxiliary alloy flakes are subjected to hydrogen crushing, dehydrogenation, and grinding to prepare high-Ce auxiliary alloy powder.

[0033] According to an embodiment of the present invention, the mass ratio of the powder of the low-Ce main alloy to the powder of the high-Ce auxiliary alloy is (1-50):1, for example, 1:1, 5:1, 10:1, 20:1.

[0034] According to an embodiment of the present invention, the pressing and molding comprises mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy and then pressing and molding the mixture under a magnetic field to obtain a green body.

[0035] Preferably, the magnetic field can be a magnetic field known in the art, such as a magnetic field with a magnetic field strength of 2T.

[0036] According to an embodiment of the present invention, the compression molding can be performed using a device known in the art, such as in a press mold cavity.

[0037] According to the embodiment of the present invention, after the pressing and forming, the green body may be subjected to a cold isostatic pressing treatment to further increase the green body density.

[0038] According to an embodiment of the present invention, the sintering process comprises heating the green body to 1000-1100° C. in a vacuum atmosphere to obtain a green body.

[0039] According to an embodiment of the present invention, the composite diffusion treatment comprises: arranging diffusion materials on the surface of the green body and performing heat treatment.

[0040] According to an embodiment of the present invention, the diffusion material can be arranged on the surface of the blank by a method known in the art, and the present invention does not make any specific limitation.

[0041] According to an embodiment of the present invention, the slurry containing the diffusion material is uniformly coated on the surface of the green body.

[0042] According to an embodiment of the present invention, the diffusion material includes RH and RL, and optionally M powder is added or not added.

[0043] Preferably, the RH is selected from at least one of heavy rare earth metals such as Dy, Tb, and Ho.

[0044] Preferably, the RL is selected from at least one of light rare earth metals such as Pr and Nd.

[0045] Preferably, the M powder is selected from Ga and / or Cu.

[0046] According to an embodiment of the present invention, the diffusion material comprises the following components: RH content is 20-70wt%, RL content is 20-70wt%, and M powder content is 0-10wt%.

[0047] Preferably, in the diffusion material, the mass ratio of RH, RL and M powder is (1-10):(1-5):(0-2), for example, 8:3:0, 4:4:0, 4:3.5:0.5.

[0048] According to an embodiment of the present invention, the RH and RL are provided by powder of RH and powder of RL, respectively.

[0049] Preferably, the powder of RH is selected from at least one of a single metal of RH, an alloy of RH, an oxide, a fluoride, a hydride, and an oxyfluoride of RH. Exemplarily, the powder of RH is selected from at least one of a single metal, an alloy, an oxide, a fluoride, a hydride, and an oxyfluoride of Dy. Exemplarily, the powder of RH is selected from at least one of a single metal, an alloy, an oxide, a fluoride, a hydride, and an oxyfluoride of Tb. Exemplarily, the powder of RH is selected from at least one of a single metal, an alloy, an oxide, a fluoride, a hydride, and an oxyfluoride of Ho.

[0050] Preferably, the powder of RL is selected from at least one of a single metal of RL, an alloy of RL, an oxide of RL, a fluoride of RL, a hydride of RL, and an oxyfluoride of RL. Exemplarily, the powder of RL is selected from at least one of a single metal, an alloy, an oxide, a fluoride, a hydride, and an oxyfluoride of Pr. Exemplarily, the powder of RL is selected from at least one of a single metal, an alloy, an oxide, a fluoride, a hydride, and an oxyfluoride of Nd.

[0051] According to an embodiment of the present invention, a diffusion aid and / or a solvent may be added to the diffusion material. The diffusion aid and the solvent are selected from materials known in the art. For example, the diffusion aid is 4-hexylresorcinol and the solvent is ethanol.

[0052] Preferably, in the present invention, there is no specific limitation on the amount of the diffusion aid and / or solvent used, as long as the diffusion of the diffusion material can be achieved.

[0053] Exemplarily, in the diffusion material, the mass ratio of RH, diffusion aid and solvent is (1-5):(0-3):(0-3), for example, 4:2:1.

[0054] In the present invention, since there are obvious differences in composition between the composite main phase grains and within a single composite main phase grain, the heterogeneity of the chemical composition and distribution causes short-range strong exchange and long-range static magneto-coupling to exist inside the magnet, effectively improving the nucleation field of the magnet's reverse magnetization domain, inhibiting the nucleation of the reverse magnetization domain, and hindering the expansion of the reverse magnetization domain, thereby significantly improving the coercive force of the magnet.

[0055] However, when permanent magnets are prepared using a single alloy process of Ce or Nd and a composite diffusion process, or when permanent magnets are prepared using a double alloy process of Nd and Ce and an RH diffusion process, the same performance level cannot be achieved, because the components of the main phase grains are basically the same and homogeneous, and long-range static magneto coupling cannot be formed. Therefore, under the same composition and process conditions, Hcj performance equivalent to that of the present invention cannot be obtained.

[0056] The present invention also provides application of the permanent magnet, for example, application in a motor.

[0057] Beneficial Effects

[0058] 1. The permanent magnet prepared by the present invention includes two different composite main phase grains. The long-range static magneto coupling between the grains and the short-range strong exchange effect inside a single composite main phase grain make the magnet have high coercive force magnetic properties.

[0059] 2. The present invention can ensure that the heavy rare earth elements arranged on the surface of the magnet diffuse deeper and have better diffusion effect through composite diffusion treatment, so that the core of the magnet far away from the surface (i.e. 500 μm away from the surface) also has the above-mentioned composite phase structure characteristics, so that the organization of the entire magnet presents uniform distribution, effectively improving the coercive force and squareness of the magnet, and significantly improving the magnet's ability to resist high-temperature demagnetization.

[0060] 3. In addition, the present invention effectively reduces the melting point of the grain boundary phase through the composite diffusion source, increases the diffusion channel of the heavy rare earth elements, and improves the diffusion distance of the heavy rare earth elements in the magnet, ensuring that each microscopic region in the magnet can form composite main phase grains, improving the uniformity of the organizational structure distribution, thereby further improving the Hcj and squareness of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 Schematic diagram of the main phase and grain boundary phase characteristics of the magnet surface layer of Example 1-1.

[0062] Figure 2 This is the scanning electron microscope backscattering image of the magnet core (50 μm away from the magnet surface) of Example 1-1.

[0063] Figure 3 EPMA images of Dy and Pr elements on the cross section of the magnet core (50 μm from the magnet surface) of Example 1-1 (a is the Dy element distribution map, b is the Pr element distribution map).

[0064] Figure 4 This is an EPMA graph of a linear scan of the Ce element content through the main phase grains on a cross section of the magnet core (50 μm from the magnet surface) of Example 1-1.

[0065] Figure 5 The following are the SEM backscattering image (a) of the magnet core (50 μm away from the magnet surface) of Comparative Example 1-1 and the EMPA image (b) of the Dy element on the cross section of the core. DETAILED DESCRIPTION

[0066] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0067] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0068] Example 1-1

[0069] The preparation method of R-Fe-B permanent magnet is as follows:

[0070] (1) Preparation of alloy flakes: According to the compositions of the main phase alloy and the auxiliary phase alloy as shown in Table 1, the raw materials were weighed respectively, and the main phase alloy flakes and the auxiliary phase alloy flakes were prepared in the following manner: a vacuum induction melting furnace was used for smelting under the protection of an Ar gas atmosphere, and the molten liquid was cast onto a quenching roller with a rotation speed of 32 rpm. The liquid casting temperature was 1400°C, and main phase alloy flakes with an average thickness of 0.25 mm and auxiliary phase alloy flakes with an average thickness of 0.30 mm were prepared.

[0071] (2) Preparation of alloy powder: The main phase alloy flakes and the auxiliary phase alloy flakes are subjected to hydrogen crushing, dehydrogenation, and air flow grinding to prepare the main phase alloy powder and the auxiliary phase alloy powder with average particle sizes of 3.0 μm and 2.8 μm, respectively.

[0072] The main phase alloy powder and the auxiliary phase alloy powder are mixed under the protection of N2 gas atmosphere, and the mass ratio of the two is 3:1, and 0.05wt% of anti-oxidation lubricant is added, and the mixture is stirred and mixed evenly;

[0073] (3) Pressing: Fill the mixed powder into the mold cavity of the pressing equipment under the protection of N2 gas atmosphere, press it in the orientation magnetic field with a field strength of 3T, and then perform isostatic pressing at a pressure of 180 MPa in an isostatic press to obtain a green compact;

[0074] (4) Sintering treatment: placing the green compact obtained in step (3) in a vacuum sintering furnace, heating the green compact to 300-400°C at a heating rate of 3°C / min, heating the green compact to 670°C at a heating rate of 5°C / min, maintaining the temperature at 670°C for 70 min, and then heating the green compact to 1040°C at a heating rate of 8°C / min for sintering treatment for 5 h, continuing the first stage aging treatment at 900°C for 4 h, and then performing the second stage aging treatment at 530°C for 3 h to obtain a sintered green compact;

[0075] Processing the above green body into a sheet with a size of 40*25 mm, wherein the thickness in the orientation direction is 5 mm;

[0076] (5) Diffusion treatment: Dy single metal, Pr single metal, 4-hexylresorcinol and ethanol are mixed in a mass ratio of 4:4:2:1. Then, they are mechanically stirred and mixed for 2 hours to obtain a diffusion slurry containing Dy and Pr; the above diffusion slurry is evenly coated on the surface of the thin sheet obtained in step (4), and the coating amount is 1% of the mass of the substrate magnet. The thin sheet is dried at 60°C for 5 minutes to obtain a thin sheet coated with Dy and Pr metal diffusion sources. Subsequently, vacuum infiltration is performed at 740°C for 4 hours, and then vacuum infiltration is continued at 930°C for 6 hours. After vacuum aging treatment is performed at 500°C for 4.5 hours, R-Fe-B permanent magnet M1 after Dy and Pr mixed diffusion treatment is obtained.

[0077] Table 1 Raw materials of Examples 1-1 to 1-4

[0078] PcqI Ce Tb Co Al Ti Cu Ga Zr B Main phase alloy 30 0 1 1 0.5 0.2 0.1 0.4 0.2 1 Auxiliary phase alloy 17 15 0 1 0.2 0 0.3 0 0 0.98

[0079] Example 1-2

[0080] The method for preparing the permanent magnet of this embodiment is basically the same as that of Embodiment 1-1, except that Pr in the diffusion slurry of step (5) is replaced by Nd.

[0081] Examples 1-3

[0082] The permanent magnet preparation method of this embodiment is basically the same as that of Embodiment 1-1, except that the diffusion slurry in step (5) also includes Cu, and the diffusion slurry is mixed according to the mass ratio of Dy single metal, Pr single metal, Cu metal, 4-hexylresorcinol and ethanol of 4:3.5:0.5:2:1.

[0083] Comparative Example 1-1

[0084] The method for preparing the permanent magnet of this comparative example is basically the same as that of Example 1-1, except that the diffusion slurry in step (5) does not include Pr.

[0085] The magnetic property test results of the sintered green body in Example 1-1 and the permanent magnets prepared in Examples 1-1 to 1-4 are shown in Table 2.

[0086] Table 2 Magnetic properties of Examples 1-1 to 1-3 and Comparative Example 1-1

[0087] Diffusion Materials HkDJ Br Squareness Sintered green body / 1275 1.353 0.985 Example 1-1 Dy-Pr 1795 1.334 0.971 Example 1-2 Dy-Nd 1805 1.337 0.973 Examples 1-3 Dy-Pr-Cu 1810 1.332 0.977 Comparative Example 1-1 Dy 1671 1.341 0.951

[0088] Figure 1 Schematic diagram of the main phase and grain boundary phase characteristics of the surface layer of the permanent magnet of Example 1-1.

[0089] Figure 2 Schematic diagram of the main phase and grain boundary phase characteristics of the core (500 μm from the magnet surface) of the permanent magnet of Example 1-1.

[0090] Figure 3 EPMA images of Dy and Pr elements on the cross section of the magnet core (50 μm from the magnet surface) of Example 1-1 (the left image is the Dy element distribution map, and the right image is the Pr element distribution map)

[0091] Figure 4 This is an EPMA graph of a linear scan of the Ce element content through the main phase grains on a cross section of the magnet core (50 μm from the magnet surface) of Example 1-1.

[0092] from Figure 1 to Figure 4 It can be seen that the permanent magnet includes at least grain boundaries and composite main phase grains; the grain boundaries include RH-rich phases, and the RH-rich phases are distributed in agglomerates within the grain boundaries between the composite main phase grains, preferably at the intersection of any three or more adjacent composite main phase grains, and the RH-rich phases are continuously distributed along the grain boundaries in the form of thin layers and bands.

[0093] Depend on Figure 2 , Figure 3 It can be seen that the RH-rich phase in the permanent magnet is a bright white area in the backscattering imaging mode of the scanning electron microscope, distributed between adjacent main phase particles or at the junction of three or more main phase particles, and its RH content is greater than the RH content in the main phase grains.

[0094] Depend on Figure 2 , Figure 4 It can be seen that the composite main phase grains include Ce-rich main phase grains and Ce-poor main phase grains, which are dark gray areas in the scanning electron microscope backscattering imaging mode; the Ce content in the Ce-rich main phase grains is: 14.5wt%; the Ce content in the Ce-poor main phase grains is: 0.5wt%.

[0095] Depend on Figure 2 , Figure 3 It can be seen that the composite main phase grains are a core-shell structure; among them, the shell structure is a light gray area in the scanning electron microscope backscattering imaging mode, which is enriched with RL elements, and the content of RL in the shell structure is greater than or equal to the content of RL in the core structure.

[0096] also, Figure 3 This is the distribution diagram of Dy element on the cross section of the magnet core (50 μm from the magnet surface) of Example 1-1. Figure 5 The Dy element distribution diagram on the cross section of the magnet core (50 μm from the magnet surface) of Comparative Example 1-1. Figure 3 and Figure 5 It can be seen that Example 1-1 and Comparative Example 1-1 use the same composition of sintered green bodies for composite diffusion. Figure 3 and 4The measurement results show that the change of the diffusion treatment method does not cause the change of the Dy content inside the magnet along the diffusion direction, but the coercive force inside the magnet is greatly improved. The inventor believes that the reason for the difference in the coercive force of the permanent magnet obtained by the two diffusion methods is not due to the concentration gradient, but the microstructure is different. By observing the cross section at 50 μm from the magnet surface, it can be seen that the Dy element in the sample of Example 1 forms a more continuous enriched stripe along the grain boundary, while the Dy element in the sample of Comparative Example 1 is not enriched at the grain boundary, but through the diffusion substitution process, causing the Dy element to be replaced inside the main phase. This is because when RL is contained in the diffusion material, it is easier to diffuse into the main phase than RH, so that the main phase forms a core-shell structure, and the RL content in the shell structure on its surface is high, which can avoid the RH in the diffusion material from being replaced in the main phase structure, so the Dy element can diffuse to the core of the permanent magnet along the grain boundary.

[0097] From the above analysis, it can be seen that the RH element in the grain boundary phase of the permanent magnet prepared by the present invention can diffuse to the core position deeper in the surface layer of the magnet, indicating that the composite diffusion effect of the present invention is good.

[0098] Example 2-1

[0099] The method for preparing the permanent magnet of this embodiment is basically the same as that of Embodiment 1-1, except that the raw materials are weighed respectively according to the compositions of the main phase alloy and the auxiliary phase alloy as shown in Table 3.

[0100] Table 3 Raw materials of Examples 2-1 to 2-3 and Comparative Example 2-1

[0101] PcqI Ce Tb Co Al Ti Cu Ga Zr B Main phase alloy 30 1 1 1 0.5 0.2 0.1 0.4 0.2 1 Auxiliary phase alloy 17 15 0 1 0.2 0 0.3 0.0 0 0.98

[0102] Example 2-2

[0103] The method for preparing the permanent magnet of this embodiment is basically the same as that of Embodiment 2-1, except that Pr in the diffusion slurry of step (5) is replaced by Nd.

[0104] Example 2-3

[0105] The permanent magnet preparation method of this embodiment is basically the same as that of Embodiment 2-1, except that the diffusion slurry in step (5) also includes Cu, and the diffusion slurry is mixed according to the mass ratio of Dy single metal, Pr single metal, Cu metal, 4-hexylresorcinol and ethanol of 4:3.5:0.5:2:1.

[0106] Comparative Example 2-1

[0107] The method for preparing the permanent magnet of this comparative example is basically the same as that of Example 2-1, except that the diffusion slurry in step (5) does not include Pr.

[0108] The magnetic property test results of the sintered green body of Example 2-1 and the permanent magnets prepared in Examples 2-1 to 2-4 are shown in Table 4.

[0109] Table 4 Magnetic properties of Examples 2-1 to 2-3 and Comparative Example 2-1

[0110] Diffusion Materials HkDJ Br Squareness Sintered green body / 1215 1.344 0.986 Example 2-1 Dy-Pr 1720 1.315 0.970 Example 2-2 Dy-Nd 1730 1.311 0.974 Example 2-3 Dy-Pr-Cu 1732 1.313 0.978 Comparative Example 2-1 Dy 1628 1.321 0.953

[0111] It can be seen from Tables 3 and 4 that when the composite diffusion material includes RH and RL, the Hcj of the permanent magnet increases significantly.

[0112] Comparative Example 3

[0113] The method for preparing the permanent magnet of this comparative example is basically the same as that of Example 1-1, except that the raw materials are weighed respectively according to the compositions of the main phase alloy and the auxiliary phase alloy as shown in Table 5.

[0114] Table 5 Raw materials list of comparative example 3

[0115] PcqI Ce Tb Co Al Ti Cu Ga Zr B Main phase alloy 30 1.5 1 1 0.5 0.2 0.1 0.4 0.2 1 Auxiliary phase alloy 17 15 0 1 0.2 0 0.3 0.0 0 0.98

[0116] The magnetic properties test results of the sintered green body and permanent magnet prepared in Comparative Example 3 are shown in Table 6.

[0117] Table 6 Magnetic properties of comparative example 3

[0118] Diffusion Materials HkDJ Br Squareness Sintered green body 1201 1.339 0.985 Comparative Example 1 Dy-Pr 1589 1.312 0.947

[0119] By comparing Table 2, Table 4 and Table 6, it can be seen that when Ce in the main phase alloy is 0-1%, composite diffusion is carried out and the performance is improved significantly, while when the main phase alloy is not in this range, the coercive force of the sintered green body is limited.

[0120] Comparative Example 4

[0121] The method for preparing the permanent magnet of this comparative example is basically the same as that of Example 1-1, except that the alloy is prepared by weighing the raw materials shown in Table 7, that is, the main phase alloy and the auxiliary phase alloy are not used to prepare the green body.

[0122] Table 7 Raw materials list of comparative example 4

[0123] PcqI Ce Tb Co Al Ti Cu Ga Zr B Alloy composition 28 3.75 0.75 1 0.43 0.15 0.15 0.3 0.15 1

[0124] The magnetic properties test results of the sintered green body and permanent magnet prepared in Comparative Example 4 are shown in Table 8.

[0125] Table 8 Magnetic properties of Comparative Example 4

[0126] Diffusion Materials HkDJ Br Squareness Sintered green body 1005 1.338 0.988 Comparative Example 4 Dy-Pr 1221 1.313 0.941

[0127] Comparative Example 4 uses a conventional method to prepare a permanent magnet containing Ce, that is, Ce raw materials are directly added during smelting without using a main phase alloy and an auxiliary phase alloy to prepare a green body. As can be seen from Table 8, even if the composite diffusion treatment of the present invention is used for the sintered green body prepared by the conventional method, the coercive force of the permanent magnet is limited.

[0128] The inventors discovered that due to the obvious differences in composition between the composite main phase grains and within a single composite main phase grain, the heterogeneity of chemical composition and distribution causes short-range strong exchange interactions and long-range static magneto-coupling interactions inside the magnet, effectively enhancing the nucleation field of the magnet's reverse magnetization domains, inhibiting the nucleation of reverse magnetization domains, and hindering the expansion of reverse magnetization domains, thereby significantly improving the coercive force of the magnet.

[0129] However, when permanent magnets are prepared using a single alloy process of Ce or Nd and a composite diffusion process, or when permanent magnets are prepared using a double alloy of Ce and Nd and an RH diffusion process, the same performance level cannot be achieved, because the components of the main phase grains are basically the same and homogeneous, and long-range static magneto coupling cannot be formed. Therefore, under the same composition and process conditions, Hcj performance equivalent to that of the present invention cannot be obtained.

[0130] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A R-Fe-B permanent magnet, characterized in that: The permanent magnet at least includes grain boundaries and composite main phase grains; The grain boundary includes an RH-rich phase, which is distributed in the form of agglomerates in the grain boundary between the composite main phase grains and at the intersection of any three or more adjacent composite main phase grains; the RH-rich phase is distributed continuously along the grain boundary in the form of a thin layer band; The content of RH in the grain boundary is greater than the content of RH in the main phase grains, and RH is selected from at least one of Dy, Tb, and Ho heavy rare earth metals; The composite main phase grains have a core-shell structure, the core-shell structure includes a core structure with an RTB-type phase structure and a shell structure on the outer layer of the core structure; the content of RH in the grain boundary is greater than the content of RH in the shell structure; the content of RL in the shell structure is greater than or equal to the content of RL in the core structure; RL is selected from at least one of Pr and Nd light rare earth metals; The core structure includes Ce-rich main phase grains and Ce-poor main phase grains; the Ce content in the Ce-rich main phase grains is greater than 1 and not greater than 15wt%; the Ce content in the Ce-poor main phase grains is 0-1wt%; The permanent magnet has a phase structure of grain boundaries and composite main phase grains from the surface to the core, and the core of the permanent magnet refers to a position at least 500 μm away from the magnet surface.

2. The R-Fe-B permanent magnet according to claim 1, characterized in that: The RTB type phase structure includes at least the following components: R, whose weight percentage is 28%≤R≤35%; R is selected from neodymium and cerium, and optionally includes or excludes at least one of scandium, yttrium, lanthanum, cerium, praseodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium; B, the weight percentage of which is 0.8%≤B≤1.2%; M, whose weight percentage is 0≤M≤5%; M is selected from at least one of aluminum, titanium, copper, gallium, zirconium and niobium; The balance is T; T is selected from iron, and optionally includes or excludes cobalt.

3. The R-Fe-B permanent magnet according to claim 1, characterized in that: The R-Fe-B permanent magnet is prepared by mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy, pressing and molding, sintering, and then performing composite diffusion.

4. The R-Fe-B permanent magnet according to claim 3, characterized in that: In the low-Ce main alloy, the content of Ce is not more than 1wt%; In the high-Ce auxiliary alloy, the content of Ce is greater than 1wt% and not greater than 15wt%.

5. The method for preparing the R-Fe-B permanent magnet according to any one of claims 1 to 4, characterized in that: The preparation method comprises the steps of mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy, pressing and molding the mixture, and sintering the mixture to obtain a green body, and preparing the permanent magnet through composite diffusion of the green body.

6. The preparation method according to claim 5, characterized in that: In the low-Ce main alloy, the content of Ce is not more than 1wt%; In the high Ce auxiliary alloy, the Ce content is greater than 1wt% and not greater than 15wt%; The mass ratio of the powder of the low-Ce main alloy to the powder of the high-Ce auxiliary alloy is (1-50):

1.

7. The preparation method according to claim 5, characterized in that: In the low-Ce main alloy, the Ce content is 0-1wt%.

8. The preparation method according to claim 5, characterized in that: The pressing and molding comprises mixing powder of a low-Ce main alloy and powder of a high-Ce auxiliary alloy, and then pressing and molding under a magnetic field to obtain a green compact; After pressing and forming, it is also subjected to cold isostatic pressing to further increase the density of the green body; The sintering process includes heating the green body to 1000-1100° C. in a vacuum atmosphere to obtain a green body.

9. The preparation method according to claim 5, characterized in that: The composite diffusion treatment includes: arranging diffusion material on the surface of the blank and performing heat treatment; The diffusion material includes RH and RL, and optionally M powder is added; The RH is selected from at least one of heavy rare earth metals Dy, Tb, and Ho; The RL is selected from at least one of Pr and Nd light rare earth metals; The M powder is selected from Ga and / or Cu.

10. The preparation method according to claim 9, characterized in that: The slurry containing the diffusion material is uniformly coated on the surface of the green body.

11. The preparation method according to claim 9, characterized in that: The diffusion material comprises the following components: RH content is 20-70wt%, RL content is 20-70wt%, and M powder content is 0-10wt%; In the diffusion material, the mass ratio of RH, RL and M powder is (1-10):(1-5):(0-2).

12. The preparation method according to claim 9, characterized in that: The RH and RL are provided by RH powder and RL powder, respectively; The RH powder is selected from at least one of a single metal of RH, an alloy of RH, an oxide of RH, a fluoride, a hydride, and an oxyfluoride; The powder of RL is selected from at least one of a single metal of RL, an alloy of RL, an oxide of RL, a fluoride of RL, a hydride of RL, and a fluoride oxide of RL.

13. Use of the R-Fe-B permanent magnet according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Rare Earth Permanent Magnet And Method For Manufacturing Thereof

    CN105788839A

  • Preparation method of sintered neodymium iron boron magnet

    CN107026003A

  • High-coercivity neodymium-cerium-iron-boron permanent magnet and preparation method and application thereof

    CN114284019A